PRODUCTION OF SINGLE CELL OIL FROM LOCAL FUNGAL ISOLATE - Al – Shamary, E. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Twenty fungal isolates have been isolated  from different sources, soils( Some of them were contaminated with mineral oils)  wheat, rice bran and rotting sesame seeds. Five isolates contained several  highly lipidic particles. The highest lipid amount (5.95 g/L) was obtained from Mucor sp. that isolated from soil which was contaminated with mineral oils and the oil yield was 50% of biomass. The results indicated that all carbon resources gave more than 20% lipid. The best carbon source for lipid production was Glucose and then Xylose which gave 50% and 46% oil respectively. The best sources of nitrogen were yeast extract and  NH4Cl which were achieved 54% and 50% oil respectively. Regarding the incubation period, it has been noticed that a temperature range 20 - 30 C ᵒwas favorable for oil production and the  highest  percentage ( 55.5%) was obtained at 25 Cᵒ. The optimum pH for lipid production was 6.5, it gave 56% oil. The optimum condition for lipid production in respect to size of inoculum, agitation rate, and incubation duration were 1 X 107 spore/ml, 150 rpm, 120h respectively. This condition achieved 56.5%,  58% and 68% oil respectively.